Adaptation to the School Enviroment in Early Elementary Education - Diana Borbélyová (Paidagogos - Society For Philosophy, Theory and Praxis of Education, 2017)
The study deals with the topical issue of school adaptation. It examines the individual aspects of adaptation in early elementary education. Special attention is paid to adaptation problems and their prevention. The aim of the contribution is to provide information about the contemporary approach to the issue and present some strategies which may be applied in practice in order to reduce the incidence of adaptation problems.